KEBIJAKAN HUKUM DI TENGAH PENANGANAN WABAH CORONA VIRUS DISEASE (COVID-19) - Julaiddin, Julaiddin; Sari, Henny Puspita (UNES Law Review, 2020)
The handling of Covid-19 nationally is a unified action born of a comprehensive strategic policy. This policy should address the current state and anticipate its impact later. The efforts currently undertaken by the Government are: social distancing/physical distancing policy, protection for healthcare workers as the front guard, social restrictions on large-scale, government transparency in the handling of Covid-19 pandemic, the validity of the test result data. For the treatment of this Covid-19 outbreak, law enforcement became one of the steps chosen by the government. The police officers are tasked with dissolving crowds, dealing with a liar or hoax, as well as a hoarders of staple material. In addition the police have also prepared a criminal threat for the violating community, the sanctions are in the information on the number of police in Mak/2/III/2020 regarding compliance with government policy in handling the spread of Corona Virus (Covid-19) and other forms of infringement or crime that may occur during PSBB in Kapolri Telegram mail number ST/1098/IV.